2019
DOI: 10.1002/jcp.28902
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA LINC00958 regulates cell sensitivity to radiotherapy through RRM2 by binding to microRNA‐5095 in cervical cancer

Abstract: Long noncoding RNAs (lncRNAs) have been implicated in the regulation of resistance to radiotherapy in cervical cancer, which is a type of gynecological disease with high mortality in women around the world. Hence, our purpose is to delineate the involvement of LINC00958 in regulating cell sensitivity to radiotherapy in cervical cancer. LINC00958 expression in cervical cancer was assayed, followed by verification of the relationship among LINC00958, microRNA-5095 (miR-5095) and ribonucleotide reductase subunit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 23 publications
6
40
0
Order By: Relevance
“…The inhibitory effects of LINC00958 knockdown on LAD cells proliferation, migration and invasion revealed the oncogenic properties of LINC00958 in LAD. This observation showed similarity to the reports of enriched present research on the oncogenic nature of LINC00958 in pancreatic cancer, gastric cancer (GC) and cervical cancer [26][27][28].…”
Section: Discussionsupporting
confidence: 91%
“…The inhibitory effects of LINC00958 knockdown on LAD cells proliferation, migration and invasion revealed the oncogenic properties of LINC00958 in LAD. This observation showed similarity to the reports of enriched present research on the oncogenic nature of LINC00958 in pancreatic cancer, gastric cancer (GC) and cervical cancer [26][27][28].…”
Section: Discussionsupporting
confidence: 91%
“…Nowadays, a variety of lncRNAs are known to be dysregulated in cervical cancer. [54][55][56] Accumulating evidence has confirmed the contribution of lncRNA dysregulation to the aggressiveness of cervical cancer, although only a few lncRNAs have been validated as being involved in cervical cancer. [57][58][59] Therefore, identifying the lncRNAs associated with cervical cancer will improve our knowledge of the role of lncRNAs in the malignancy of cervical cancer, thus highlighting their usefulness as therapeutic and/or prognostic targets in cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive research has confirmed aberrant expression of lncRNAs in cervical cancer. 21,47,48 The dysregulation of lncRNAs has been demonstrated to be crucial for cervical carcinogenesis and cervical cancer progression through the control of a wide range of aggressive characteristics of cancer cells. [49][50][51] Accordingly, lncRNAs may be promising RNAs for the identification of novel chemotherapeutic medications.…”
Section: Discussionmentioning
confidence: 99%
“…Functionally, the aberrantly expressed lncRNAs exert cancer-inhibiting or cancer-promoting actions and thereby serve as critical modulators of cervical carcinogenesis by affecting a number of malignant characteristics. [21][22][23] Therefore, an in-depth understanding of the functions of lncRNAs in cervical cancer is crucial for improving the disease diagnosis, prognosis, and treatments.…”
Section: Introductionmentioning
confidence: 99%